Notes on Vernonia pratensis Klatt (Asteraceae: Vernonieae) - Loeuille, Benoît; Antonio-Domingues, Higor; Larridon, Isabel; Razafiniary, Velosoa; Misa, Andry Ny Aina Ary; Andriamanohera, Mihajamalala Andotiana; Gostel, Morgan R; Simões, Ana Rita Giraldes (Phytotaxa, 2025)
Vernonia (Asteraceae: Vernonieae) is monophyletic if circumscribed to include only a North American clade of ca. 20 species. Vernonia pratensis, an endemic species of Madagascar, has been placed in the synonymy of Cyanthillium patulum or considered a distinct species in Bothriocline. In this study we characterise the pollen and cypsela of Vernonia pratensis, Bothriocline longipes, and Cyanthillium patulum with details on morphology and ultra-sculpture. The pollen grains of these species are 3-brevicolporate or 3-porate and echinolophate; in B. longipes and V. pratensis there is an inconspicuous colpus formed by interlacunar gaps (absent in C. patulum). The cypselae of B. longipes and V. pratensis have prominent ribs, broader or equally as wide as the grooves and that are fused into a shallow, apical rim; the grooves are covered by unicellular trichomes (type 1) with a striate cuticle. By contrast, the cypselae of C. patulum have ribs narrower than the grooves and not fused apically; the grooves are covered by infundibular idioblasts, and bilobed glandular trichomes at the base. Based on these morphological findings, V. pratensis is here placed in Bothriocline and named B. madagascariensis. This is the single species that occurs in Madagascar within a genus of ca. 50 species otherwise restricted to Tropical Africa and subtropical Southern Africa. Full palynological descriptions, measurements, and scanning electron microscopy (SEM) and light microscopy (LM) images are provided for the three species (B. longipes, B. madagascariensis, and C. patulum), as well as a full taxonomic description of B. madagascariensis, with a preliminary conservation status assessment, nomenclatural notes, and a discussion of possible relationships with other species of Bothriocline.